Patient portal functionalities and uptake: systematic review protocol (Preprint) - Alturkistani,A; Greenfield,G; Greaves,F; Aliabadi,S; Jenkins,RH; Costelloe,C (JMIR Publications, 2019)
Background:Patient portals are digital health tools adopted by healthcare organisations. The portals are generally connected to the electronic health record of the healthcare organisation and offer patients functionalities such as access to the medical record, ability to order repeat prescriptions, make appointments or message the healthcare provider. Research shows that there are many potential benefits of using patient portals both for patients and for the healthcare system. Patient portals can widely differ from one context to another due to differences in the portal functionalities and capabilities. Current research reports patient portal uptake but does not explicitly specify the patient portal functionalities.Objective:The aim of the review is to identify the functionalities of electronic patient portals offered globally in primary care and secondary care both and determine its association with patient portal uptake and facilitators and barriers of its use.Methods:Medline, Embase, Scopus, PsycINFO, IEEE Xplore Digital Library, and CINAHL will be searched for relevant literature. The review inclusion criteria will be studies about patients or other portal users such as carers, studies only about tethered patient portals, studies with or without a comparator. We will report patient portal uptake numbers based on the patient portal functionalities. We will also look at facilitators and barriers to using patient portals. All primary study types will be included. Risk of bias of included studies will be assessed using the Cochrane Collaboration’s tool for assessing risk of bias in randomised trials and the National Heart, Lung, and Blood Institute Institute’ quality assessment tools. Data will be synthesised using narrative synthesis and will be reported according to the patient portal functionalities, country and healthcare system model.Results:Searches will be conducted in June 2019, and the review is anticipated to be complete by November 2019.Conclu